Islam in China: History, Spread and Culture, A Pictorial Book - Min Ke-qin@ Omar Min (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2020)
Many publications are available on the history of Islam in China, especially in English language. So, one wonders what new findings are left to be added to this field. The pictorial book under review does not offer any new information on the subject, but it does serve a purpose. In the words of the book’s Editor, Haji Koya Kutty, it is to provide general readers with “a basic idea on the history and spread of Islam in China” (p. viii) through articles gathered from various sources. Illustrated with colourful photographs, the publication would be a good coffee-table book for one to have